Destructive Pseudo-neuroarthropathy Associated With Calcium Pyrophosphate Deposition. (April 2015) - Lomax, Adam; Ferrero, Andrea; Cullen, Nick; Goldberg, Andy; Singh, Dishan
Background: Calcium pyrophosphate deposition (CPPD) disease is a metabolic disorder characterized by soft tissue calcific deposits formed primarily in articular cartilage. What can result is a crystal-induced arthropathy often referred to as pseudogout, which is variable in both presentation and severity. A particularly destructive and deforming arthritis is an uncommon but well-recognized subtype of this disease. Radiologically resembling the neuroarthropathy described by Charcot, a pattern of joint fragmentation and structural collapse occurs in the absence of peripheral neuropathy. This pseudo-neuroarthropathy is rarely reported in the foot and ankle. Methods: A total of 15 cases of pseudo-neuroarthropathy involving some previously unreported joints within the foot and ankle are described in this case series of 9 patients. Results: All patients presented with disease involving multiple joints. Clinical deformity was apparent in each case, and extensive joint destruction was seen on plain radiographs. In 6 patients, histopathological CPPD disease was confirmed on tissue biopsy of the affected joints. In the remaining 3 patients a clinical diagnosis was made on the basis of the classic appearance of pseudo-neuroarthropathy in the foot, with additional recognized features of CPPD. Operative management with deformity correction using joint arthrodesis produced satisfactory clinical and radiological results. Conclusions: In the absence of peripheral neuropathy and systemic disease, the pseudo-neuroarthropathy of CPPD should be considered when a progressively deforming and destructive arthritis is seen in the foot and ankle. Level of Evidence: Level IV, case series.